Making the grade - Hay, Iain. ([S.l.] : OUP Australia and New Zealand, 2002)
A comprehensive source of information on study and communication skills for tertiary-level students. Chapters outline the whys and hows of essays, research and laboratory reports, reviews, summaries, and more. This edition includes new material on group work and amendments reflecting technological shifts.
Keywords: Academic achievement; Academic writing; Communication in education; Study skills